High Pressure Balloon Dilatation of Primary Obstructive Megaureter in Children: A Multicenter Study - Kassite, Ibtissam; Renaux Petel, Mariette; Chaussy, Yann; Eyssartier, Emilie; Alzahrani, Khalid; Sczwarc, Caroline; Villemagne, Thierry; Lardy, Hubert; Braik, Karim; Binet, Aurélien (Frontiers in Pediatrics, 2018)
Abstract Aim of the study: We described the initial experience of 4 referral centers in the treatment of primary obstructive megaureter (POM) in children, by high-pressure balloon dilatation (HPBD) of the ureterovesical junction with double JJ stenting. We managed a retrospective study, to assess its effectiveness in long-term, and we reviewed the literature concerning this approach. Methods: We reviewed the medical records of all children who underwent HPBD for POM that require surgical treatment from May 2012 to December 2017 in 4 different institutions. The primary outcome measured was ureterohydronephrosis (UHN) and its degree of improvement after the procedure. Secondary outcomes were postoperative complications and resolution of preoperative symptomatology. Main results: 42 ureters underwent HPBD for POM in 33 children, with a median age of 14.7 months – (range: 3 months – 15 years). Ureterohydronephrosis improves in 86 % of ureters after one endoscopic treatment. Three cases required a second HPBD. Four patients required surgical treatment for worsening of UHN after endoscopic treatment. The post-operative complication rate was 50 % (21 ureters). In 13 cases (61%), they were related to double J stent. The median follow-up was 24 months (2 months – 5 years) and all patients were symptom-free. Conclusion: We reported the first multicenter study and the largest series of children treated with HPBD, with an overall success rate of 92%. Endoscopic treatment can be a definitive treatment of POM since it avoided reimplantation in 90% of cases. Complications are mainly due to double J stent. Keywords Ureteral diseases; ureteroscopy; pediatric surgery; hydronephrosis; pyelonephritis